Multi-criteria optimization for the design and operation of distributed energy systems considering sustainability dimensions. (1st January 2021) - Fonseca, Juan D.; Commenge, Jean-Marc; Camargo, Mauricio; Falk, Laurent; Gil, Iván D.
Abstract: The growing concerns about climate change and energy security have led to a shift in the paradigm of the energy framework. In this regard, distributed generation offers the possibility to deal with inefficiencies in energy delivering, and the fossil fuel dependence of conventional and centralized power plants. This work presents a modeling and multi-criteria optimization strategy for designing and operating decentralized power plants including different energy vectors. The modeling approach considers the time-varying operation of the energy conversion units for responding to electricity and hydrogen demands, along with the seasonal behavior of the storage system. A multi-criteria evaluation addressing economic, environmental and social aspects was implemented. The objective functions are the total annualized cost, the CO2 emissions and the grid dependence. According to optimization results, it is highlighted the influence of the assessed criteria upon the structure and the operating policy of the power plant. Additionally, by comparing the performance of the distributed energy system with respect to a centralized scenario, it is noted the significant potential of the decentralized generation. Indeed, depending on the optimization goal, CO2 emission reduction up to 89%, and self-sufficiency up to 81% can be achieved. Highlights: Conceptual design of distributed energy systems was studied. Time-dependent energy conversion and seasonal storage were considered. Economic, environmental and social criteria were assessed. Energy system structure and operating policy depend upon the evaluated criteria. Insights for decision-making in the design of energy systems were obtained.